Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - Sanchez, M. E.; Andicoberry, S.; Trapero, A. (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
The following values have no corresponding Zotero field: publisher: Blackwell Verlag GmbH
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - SÁNCHEZ, M E; Andicoberry, S; TRAPERO, A (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content